2023
DOI: 10.1101/2023.03.11.532168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion of modern humans over the world: The origin when considering non-linearity

Abstract: Types of diversity have been known to decline linearly with the rise of geographical distance from Africa. Declines have helped to suggest the area in Africa which holds the origin for the global expansion of modern humans. Research has, at times, explored if there is a non-linear relationship between diversity and distance from Africa. A previous suggestion was that non-linearity could affect where the expansion appears to have originated. Linear analysis with Y-chromosomal microsatellite heterozygosity has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 28 publications
0
17
1
Order By: Relevance
“…Relationships between distance from Africa and diversity appear to be better shown through quadratic (than linear) trends for autosomal microsatellite heterozygosity and also mitochondrial diversity, but this is not apparent for autosomal SNP haplotype heterozygosity, X-chromosomal microsatellite heterozygosity (Cenac, 2023) and Y-chromosomal haplotype diversity (present study). Therefore, r s were used for rankings regarding autosomal SNP haplotype heterozygosity, X-chromosomal microsatellite heterozygosity, and Y-chromosomal haplotype diversity, whilst R 2 s were utilised for rankings concerning autosomal microsatellite heterozygosity and mitochondrial diversity.…”
Section: Methodscontrasting
confidence: 62%
See 3 more Smart Citations
“…Relationships between distance from Africa and diversity appear to be better shown through quadratic (than linear) trends for autosomal microsatellite heterozygosity and also mitochondrial diversity, but this is not apparent for autosomal SNP haplotype heterozygosity, X-chromosomal microsatellite heterozygosity (Cenac, 2023) and Y-chromosomal haplotype diversity (present study). Therefore, r s were used for rankings regarding autosomal SNP haplotype heterozygosity, X-chromosomal microsatellite heterozygosity, and Y-chromosomal haplotype diversity, whilst R 2 s were utilised for rankings concerning autosomal microsatellite heterozygosity and mitochondrial diversity.…”
Section: Methodscontrasting
confidence: 62%
“…To find the ranks, correlation coefficients (rs) or R 2 s were worked out concerning each variable and distances from the 99 Betti et al (2013) African origins (through the use of distances from Cenac, 2022Cenac, , 2023, who used the Betti et al origins, or distances found in the current study which used those origins toosee Method: Geographical distance). Between autosomal microsatellite and autosomal SNP haplotype heterozygosities, ranks were averaged at each origin.…”
Section: Estimating the Origin Across Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The location where the decline is at its most negative can be called the peak point (e.g., Cenac, 2022). Like has been done with correlation coefficients for relationships between genetic diversity and distance from Africa (Luca et al, 2011; Ramachandran et al, 2005), Figure 1 presents correlation coefficients ( r – blue areas) regarding X-chromosomal microsatellite heterozygosity and distance from Africa (coefficients are from Cenac, 2023a, who used diversities from Balloux et al, 2009, and distances in Cenac, 2022). The peak point is the location giving the lowermost correlation coefficient (Cenac, 2022) (green circle).…”
Section: Introductionmentioning
confidence: 99%